Pembelajaran Daring dan Masalah Ketuntasan Belajar Mata Pelajaran Bahasa Arab di Madrasah - Razak Mursyid, Abdul (Assuthur: Jurnal Pendidikan Bahasa Arab, 2022)
This article aims to discuss thoroughly about the online earning system in Indonesia and the problem of completion of learning of Arabic language subjects in Madrasah accompanied by the quality of learning based on KMA 183 of 2019. This article uses the method of library research or literature study, namely data collected through reference journals, books, theses, and others. The results of this study aim to find out the problems related to online learning and how to solve th e solution of the problem of student learning completion, especially Arabic subjects. The research results of this article are the existence of several solutions to the problem of learning completion; By knowing the purpose and strategy of learning.